Peningkatan Motorik Halus Anak Tunagrahita Melalui Menjahit Jelujur di SLB Negeri Larantuka - Ola, Katarina Deran; Wangge, Vinsensius; Selan, Ot Bil Wilson; Liunokas, Oded; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2026)
Fine motor skills play an important role in supporting the independence and learning activities of children with intellectual disabilities, but intellectual limitations and motor coordination often become obstacles in mastering these skills. This study aims to improve the fine motor skills of children with intellectual disabilities through the application of sewing skills. The study uses a classroom action research (CAR) approach with the Kemmis and McTaggart model, which is carried out in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects were three fifth-grade students with intellectual disabilities at SLB Negeri Weri Larantuka. Data were collected through sewing performance tests and student activity observation sheets. Data analysis was conducted descriptively and quantitatively by comparing fine motor skill scores in each cycle, as well as descriptively and qualitatively through observation results to see changes in student behavior and involvement during learning. The results showed an increase in fine motor skills in each cycle, as seen in the increased neatness of the stitching, accuracy in following patterns, and eye-hand coordination. At the end of cycle II, all research subjects achieved scores above the Minimum Completion Criteria (KKM). Thus, jelujur sewing skills proved to be effective as an alternative functional learning method to improve the fine motor skills of children with intellectual disabilities